Contribution of Hepatitis B to Long-Term Outcome Among Patients With Acute Myocardial Infarction: A Nationwide Study. Issue 5 (February 2016) - Kuo, Pei-Lun; Lin, Kun-Chang; Tang, Pei-Ling; Cheng, Chin-Chang; Huang, Wei-Chun; Chiang, Cheng-Hung; Lin, Hsiao-Chin; Chuang, Tzu-Jung; Wann, Shue-Ren; Mar, Guang-Yuan; Cheng, Jin-Shiung; Liu, Chun-Peng
Abstract : Abstract: Although a possible association between hepatitis B and cardiovascular disease has been identified, the impact of viral hepatitis B on long-term prognosis after an acute myocardial infarction (AMI) is uncertain. Therefore, the aim of our study was to evaluate the specific impact of viral hepatitis B on survival after a first AMI through a retrospective analysis of data from the Taiwan National Health Insurance Research Database. This was a nationwide, propensity score-matched case–control study of patients admitted to hospitals between January 2000 and December 2012 with a primary diagnosis of a first AMI. Among the 7671 prospective patients, 244 patients with a confirmed diagnosis of viral hepatitis B infection were identified. A propensity score, one-to-one matching technique was used to match 244 controls to the AMI group for analysis. Controls were matched on the following variables: sex, age, hypertension, dyslipidemia, diabetes, peripheral vascular disease, heart failure, cerebrovascular accidents, end-stage renal disease, chronic obstructive pulmonary disease, and percutaneous coronary intervention (PCI). Overall, viral hepatitis B infection did not influence the 12-year survival rate ( P = 0.98). However, survival was lower in female patients with viral hepatitis B infection compared to those without ( P = 0.03; hazard ratio, 1.79; 95% confidence interval, 1.08–2.94). Inclusion of percutaneous coronary management improved survival, independent of sex, age, or hepatitis B status. Hepatitis B infection might increase the mortality risk of female patients after a first AMI. PCI may improve the long-term survival of patients after a first AMI, regardless of sex, age, and hepatitis B status.